Pemberian Asupan Kalori Terestriksi vs. Asupan Kalori Standar yang Berlanjut pada Pasien Penyakit Kritis dengan Refeeding Syndrome: Laporan Kasus Berbasis Bukti - Hapsari, Sukma; Pribadi, Rabbinu Rangga (UI Scholars Hub, 2025)
Refeeding syndrome is a different clinical symptom and metabolic disorder that occur during the reintroduction of nutrition in chronically malnourished patients. Calorie restriction can increase survival and reduce mortality rates. This evidence-based case report was developed to examine the influence of caloric restriction on mortality, morbidity, and duration of critical illness. A literature search was performed using PubMed, EBSCOHost, ScienceDirect, and Cochrane with the keywords: “critically ill,” “restricted caloric intake,” “standard caloric intake,” “mortality,” “morbidity,” and “duration”. Articles were appraised using the University of Oxford Centre for Evidence-Based Medicine (CEBM) tools. Two studies met the inclusion criteria. The first was a randomized controlled trial, which demonstrated that protocolized caloric restriction significantly improved 60-day survival in ICU patients with refeeding syndrome (91% vs. 78%, p = 0.002), although no significant difference was observed in days alive following ICU discharge (44.8 vs. 39.9 days, p = 0.19). The second was a meta-analysis, which suggested a trend toward reduced hospital mortality with hypocaloric feeding; however, risk ratios varied widely (0.23–5.54), and 30-day mortality differences were not statistically significant (RR: 0.79–3.00). In conclusion, while caloric restriction may not significantly impact overall mortality in chronically ill patients, it appears to improve 60- to 90-day survival in critically ill ICU patients with refeeding syndrome. One study noted a reduced risk of respiratory infection, though evidence on other complications remains inconclusive. A regimen of 20 kcal/hour for at least two days may be suitable for managing refeeding syndrome. Overall, caloric restriction may offer modest clinical benefits in this specific population.